2004
DOI: 10.1111/j.1475-6773.2004.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction, Treatment Experience, and Disability Outcomes in a Population‐Based Cohort of Injured Workers in Washington State: Implications for Quality Improvement

Abstract: Objective. To determine what aspects of patient satisfaction are most important in explaining the variance in patients' overall treatment experience and to evaluate the relationship between treatment experience and subsequent outcomes. Data Sources and Setting. Data from a population‐based survey of 804 randomly selected injured workers in Washington State filing a workers' compensation claim between November 1999 and February 2000 were combined with insurance claims data indicating whether survey respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 36 publications
(40 reference statements)
1
45
0
Order By: Relevance
“…For example, injured workers in Washington State who were dissatisfied with their medical care ("less than excellent" overall treatment experience) were over 3.5 times more likely to receive time-loss compensation for work disability 6-12 months after claim filing, relative to patients who reported an "excellent" care experience (Wickizer et al 2004b). Similarly, lower levels of overall WC satisfaction (satisfaction with quality and thoroughness of medical treatment, treatment by employer, WC process, and legal system) were significantly associated with higher levels of pain-related disability 21 months post-claim settlement among low back pain claimants, after adjustment for important demographic and WC variables .…”
Section: Introductionmentioning
confidence: 95%
“…For example, injured workers in Washington State who were dissatisfied with their medical care ("less than excellent" overall treatment experience) were over 3.5 times more likely to receive time-loss compensation for work disability 6-12 months after claim filing, relative to patients who reported an "excellent" care experience (Wickizer et al 2004b). Similarly, lower levels of overall WC satisfaction (satisfaction with quality and thoroughness of medical treatment, treatment by employer, WC process, and legal system) were significantly associated with higher levels of pain-related disability 21 months post-claim settlement among low back pain claimants, after adjustment for important demographic and WC variables .…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have shown that patients' treatment satisfaction may be related to expectations and preferences for treatment, adherence to treatment and treatment success (24, 31, 37, 38). For example, Wickizer et al (38) found that, among injured employees, those who reported less satisfaction with treatment were more likely to receive compensation for inability to work.…”
Section: Patient-reported Usefulness Between Diagnostic Groupsmentioning
confidence: 99%
“…Prior studies in workers' compensation settings have assessed the timeliness of initial visits and claims, the completeness of claim forms, visit frequency among those off work, populationbased rates of spinal imaging and opioid prescribing, disability duration, and patient satisfaction. 11,[38][39][40][41][42][43] In Washington State, disability days declined by 20% after policymakers gave physicians financial incentives to communicate with employers, prescribe appropriate activity, and assess barriers to return to work. 40 Our work affirms that activity assessment and management warrant improvement.…”
Section: Discussionmentioning
confidence: 99%